2018
DOI: 10.1590/0001-3765201820180144
|View full text |Cite
|
Sign up to set email alerts
|

Hibiscus acetosella extract protects against alkylating agent-induced DNA damage in mice

Abstract: Hibiscus acetosella was shown to exert beneficial effects in humans and animal models however, the effects of this plant on DNA are unknown. The aim of this study was to determine the antigenotoxic and antimutagenic effects of H. acetosella extracts on alkylating agent methyl methanesulfonate (MMS) in vivo in mice. Initially, we performed analysis of phenolic compounds in extracts of H. acetosella by high-performance liquid chromatography (HPLC). Next, mice were divided into 8 groups and treated with distilled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The chlorogenic acid (CGA), caffeic acid (CA), delphinidin-3-sambubioside (Dp3-Sam), delphinidin-3-glucoside (Dp3-Glu), cyanidin-3-sambubioside (Cy3-Sam), all obtained from Sigma-Aldrich Co. (St. Louis, MO, USA) were identified based on the retention times of commercial standards (UV spectrum). Gallocatechin (GC) and gallic acid (GAL) were identified as described in a previous study [ 16 ] and by their UV-visible spectral characteristics.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The chlorogenic acid (CGA), caffeic acid (CA), delphinidin-3-sambubioside (Dp3-Sam), delphinidin-3-glucoside (Dp3-Glu), cyanidin-3-sambubioside (Cy3-Sam), all obtained from Sigma-Aldrich Co. (St. Louis, MO, USA) were identified based on the retention times of commercial standards (UV spectrum). Gallocatechin (GC) and gallic acid (GAL) were identified as described in a previous study [ 16 ] and by their UV-visible spectral characteristics.…”
Section: Methodsmentioning
confidence: 99%
“…In terms of pharmacological effects, Hibiscus plants have also attracted interest because of their biological activities, which include antibacterial, anti-inflammatory, antigenotoxic, hepatoprotective, and antimutagenic activities [ 13 , 14 , 15 , 16 ]. In particular, the antibacterial activity of H. sabdariffa has been well-studied as well as other biological activities of extracts of its leaves and flowers [ 4 , 17 , 18 ], while H. acetosella has been reported as having anti-inflammatory [ 12 ] and antimutagenic activity [ 16 ], but no antibacterial activity.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Vilela et al (2018) [159] analyzed the presence of phenolic compounds in extracts of H. acetosella leaves (EHa) by high-performance liquid chromatography (HPLC) and determined the antigenotoxic effect of these extracts against the damage produced by methyl methanesulfonate (MMS) in mice. The HPLC results showed the presence of caffeic acid, gallic acid, gallocatechin, coumaric acid, and 3,4-dihydroxybenzoic acid.…”
Section: Antigenotoxic Plants and Vegetablesmentioning
confidence: 99%
“…The HPLC results showed the presence of caffeic acid, gallic acid, gallocatechin, coumaric acid, and 3,4-dihydroxybenzoic acid. On the other hand, using the micronucleus test and the comet assay, they showed that the animals treated with EHa (dose of 50 mg/kg or 100 mg/kg) plus the alkylating agent significantly decreased the DNA damage [159].…”
Section: Antigenotoxic Plants and Vegetablesmentioning
confidence: 99%
“…HA leaves extracts had potential in antioxidant and free radical scavenging properties at various solvent extractions (water, methanol, and ethanol). All of extracts had good ability to scavenge and reducing power to eliminate free radicals which may be the potential of anthocyanin content in HA leaves according to previous studies that indicated the plants in Hibiscus genus always showed the antioxidant, anti-inflammation, anticancer properties and have the potentials in free radical scavenging, due to their chemical constituents which consist of flavonoids and polyphenolic compounds [23]. The differentiation of extract solvents was a factor which effected to the ability in antioxidant of the extracts.…”
Section: Resultsmentioning
confidence: 86%